Torsional diffusion Monte Carlo: A method for quantum simulations of proteins - Clary, D (2001)
Coupled torsional motions in proteins were treated by extending quantum diffusion Monte Carlo method. An algorithm and program were developed by interfacing the DMC method with all-atom force fields for proteins. The method gave atomic coordinates and zero-point energy averaged over the coupled torsional motions in the quantum ground state of the protein. Application of new algorithm was made to the proteins gp41-HIV and gelsolin . Quantum dynamical effects were found to be important for the energies and geometries of typical proteins.